2017
DOI: 10.3171/2016.2.jns152544
|View full text |Cite
|
Sign up to set email alerts
|

Patency of the posterior communicating artery following treatment with the Pipeline Embolization Device

Abstract: OBJECTIVE The Pipeline Embolization Device (PED) has become an effective treatment strategy for some cerebral aneurysms. Concerns regarding the patency of branch arteries have been raised. The objective of this study was to assess the patency of the posterior communicating artery (PCoA) following treatment of PCoA aneurysms using the PED. METHODS All patients with PCoA aneurysms treated with the PED who had angiographic follow-up were retrospectively identified. The patency of the PCoA at follow-up was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
(32 reference statements)
4
33
0
Order By: Relevance
“…Raz et al 31 described a single case of AChA coverage leading to asymptomatic occlusion for a PCoA aneurysm. FD for PCoA aneurysms resulted in occlusion of the vessel in approximately half of cases,32 with the fate of the remaining PCoAs evenly divided between diminished flow and complete patency (similar to our findings).…”
Section: Discussionsupporting
confidence: 88%
“…Raz et al 31 described a single case of AChA coverage leading to asymptomatic occlusion for a PCoA aneurysm. FD for PCoA aneurysms resulted in occlusion of the vessel in approximately half of cases,32 with the fate of the remaining PCoAs evenly divided between diminished flow and complete patency (similar to our findings).…”
Section: Discussionsupporting
confidence: 88%
“…18 Reported occlusion rates of the posterior communicating artery are more widely variable due to variability in the anatomy of the posterior communicating artery. [32][33][34][35][36][37] Factors likely associated with sidebranch occlusion include the number of PEDs covering the branch, the flow demand on that branch, and potential collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm shift in wide application has been supported by large series showing relative safety of the PED. Despite initial concerns over the occlusion of branch vessels such as the ophthalmic artery and anterior choroidal artery, multiple studies have shown that these are largely well tolerated 6 12 13. As our experience with flow diversion with the PED and other devices grows, we are developing a nuanced understanding of the appropriate applications and potential outcomes.…”
Section: Discussionmentioning
confidence: 99%